Sea surface temperature and stable isotopes of alkenones for IODP Site 321-U1338 - Katrin Hättig; Panteleimon Prokopiou; Stefan Schouten; Marcel T J van der Meer (PANGAEA, 2024)
Middle Miocene to Pleistocene (1-14.5 Ma) compound-specific hydrogen and carbon isotopes of alkenones and sea surface temperature (UK extquotesingle37) are obtained from the sediment record of Integrated Ocean Discovery Program (IODP) Expedition 321, Site U1338 drilled in the equatorial Pacific. The very depleted hydrogen isotope ratios suggest that factors other than the isotopic composition of seawater affect the hydrogen isotopic composition of alkenones. Comparison with modern Pacific Ocean data (see Wolhowe et al., 2015; Wolfshorndl et al., 2019) and analysis of carbon isotopes of alkenones suggest that subsurface production of alkenones at low light intensity had a strong impact on the hydrogen isotopic composition of alkenones.